Endogenous growth, countercyclical dividends, and asset prices - Palma Filep-Mosberger; Lorant Kaszab; Zhou Ren (Magyar Nemzeti Bank, 2023)
We study the nexus between endogenous growth and asset prices. We show that endogenous growth models with either horizontal and vertical innovation match financial data well due to countercyclical dividends which are either procyclical or acyclical in US data. Countercyclical dividends redistribute income from consumption towards investment in innovation improving growth prospects which are reflected in asset prices. In the horizontal innovation model of Kung and Schmid (2015) countercyclical dividends are the result of high monopoly markups. When markup is lowered from their benchmark 65 percent to 60 or 55 percent dividends become procyclical, the price-dividend ratio countercyclical, and the mean of the equity risk premia reduces from 290 to 82 or 46 basis points, respectively. When we introduce leisure preferences the wealth effect of technology shocks makes the aggregate dividends countercyclical as long as labour supply is not too elastic even with low values of the monopolist markup.
Keywords: E13; E31; E43; E44; E62; 330; endogenous growth; innovation; markup; asset pricing; dividends; equity premium